MEDIA OPTIMIZATION FOR THE DECOLORIZATION OF DISTILLERY EFFLUENT BY STREPTOCOCCOUS SP. - Anurag Singh1#*, Dr. Rajeeva Gaur1, Dr. Pradeep kumar Singh2, Ranjit Singh3, Dr. Deependra bahadur Singh,4 , Santosh kumar singh5 (Chelonian Research Foundation, 2023)
The wastewater released from distilleries and fermentation industries contain high BOD, COD alongwith melanoidin pigment. Melanoidin is a Xenobiotic dark brown colour compound, which is formed by the Maillard reaction between amino acid and carbonyl group of sugars. This recalcitrant compound causes soil and water pollution therefore must be treated before disposal. The aim of this study was to isolate and optimize a potential melanoidin decolorizing bacterium from natural resources for treatment of distillery effluent at industrial level. In this study a strain of Streptococus sp. was isolated from distillery nearby natural ecosystem and optimized for decolorization of distillery effluent at various physico-chemical and nutritional levels. This bacterium showed maximum decolorization, 87% at 40˚C using modified GYPE Medium i.e. 1% molasses medium (1%., Grade-C molasses, 0.2%., Yeast extract, 0.3%., Peptone, 0.05%., MgSO4, 0.05%., K2HPO4 with 3.5 OD effluent) pH-6.0 within 30 hours. This Streptococcus sp. can tolerate wide range of temperature as well as pH and survive in very less amount of carbon (0.2%) and nitrogen(0.2%) sources in submerged system. Hence, this bacterium has potential to degrade the melanoidin of distillery spent wash at industrial level for controlling environmental pollution. Key words: Decolorization, Streptococus sp., Melanoidin, Maillard reaction, Xenobiotic, Decolorization